Chromis tingting, a new species of damselfish from mesophotic coral ecosystems of southern Japan, with notes on C. mirationis Tanaka (Teleostei: Pomacentridae) - Tea, Yi-Kai; Gill, Anthony C.; Senou, Hiroshi (Zootaxa, 2019)
Chromis tingting sp. nov., is described on the basis of the holotype and three paratypes from Sagami Bay, Japan. The new species likely belongs to a complex consisting of C. mirationis, C. okamurai and C. struhsakeri, with which it shares the following character combination: dorsal rays XIV,13–14; anal rays II,12; pectoral rays 19–20; tubed lateral-line scales 15–17; two spinous procurrent rays dorsally and ventrally in the caudal fin; and a generally silvery white adult coloration. The new species differs from the other members of its complex in coloration details (particularly in juvenile coloration), and in having fewer gill rakers (5–6 + 17–20 = 22–26), and a larger eye -(13.7–19.4 % SL). The new species has previously been confused with Chromis mirationis, and the contention is herewith briefly discussed.